Automorphisms of Ordinary Differential Equations - Václav Tryhuk; Veronika Chrastinová (Abstract and Applied Analysis)
The paper deals with the local theory of internal symmetries of underdetermined systems of ordinary differential equations in full generality. The symmetries need not preserve the choice of the independent variable, the hierarchy of dependent variables, and the order of derivatives. Internal approach to the symmetries of one-dimensional constrained variational integrals is moreover proposed without the use of multipliers.